Acknowledging the primacy of continuity of care experiences in midwifery education. Issue 2 (March 2020) - Gamble, Jennifer; Sidebotham, Mary; Gilkison, Andrea; Davis, Deborah; Sweet, Linda
Abstract: Background: Continuity of midwifery care is the best maternity care model for women at any risk level, and there is a global imperative to improve access to midwifery-led care. However, diverse perspectives about how best to prepare graduates for working in midwifery continuity of care models persist. The continuity of care experience standard in Australia was anticipated to address this. Aim: To challenge the dearth of published information about the structures and processes in midwifery education programs by identifying: the educational value and pedagogical intent of the continuity of care experience; issues with the implementation, completion and assessment of learning associated with continuity of care experience; and discuss curriculum models that facilitate optimal learning outcomes associated with this experience. We discuss the primacy of continuity of care experience in midwifery education programs in Australia. Discussion: The inclusion of continuity of care experience in midwifery programs in Australia became mandatory in 2010 requiring 20, however this number was reduced to 10 in 2014. Research has shown the beneficial outcomes of continuity of care experience to both students and women. Continuity of care experience builds mutual support and nurturing between women and students, fosters clinical confidence, resilience, and influences career goals. We require curriculum coherence with both structural and conceptual elements focusing on continuity of care experience. Implications and recommendations: Education standards that preference continuity of care experience as the optimal clinical education model with measurable learning outcomes, and alignment to a whole of program philosophy and program learning outcomes is required.